Reassessment of the clinical impact of preformed donor‐specific anti‐HLA‐Cw antibodies in kidney transplantation. Issue 5 (18th January 2020) - Visentin, Jonathan; Bachelet, Thomas; Aubert, Olivier; Del Bello, Arnaud; Martinez, Charlie; Jambon, Frédéric; Guidicelli, Gwendaline; Ralazamahaleo, Mamy; Bouthemy, Charlène; Cargou, Marine; Congy‐Jolivet, Nicolas; Nong, Thoa; et al.
Abstract : Anti‐denatured HLA‐Cw antibodies are highly prevalent, whereas anti‐native HLA‐Cw antibodies seem to lead to random flow cytometry crossmatch results. We aimed to reassess crossmatch prediction for anti‐HLA‐Cw using 2 types of single antigen flow beads (classical beads and beads with diminished expression of denatured HLA), and to compare the pathogenicity of preformed anti‐denatured and anti‐native HLA‐Cw antibodies in kidney transplantation. We performed 135 crossmatches with sera reacting against donor HLA‐Cw (classical beads fluorescence ≥500); only 20.6% were positive. Forty‐three (31.6%) were anti‐denatured HLA antibodies (beads with diminished expression of denatured HLA fluorescence <300); all were crossmatch negative. The correlation between classical beads fluorescence and the crossmatch ratio was low (ρ = 0.178), and slightly higher with beads with diminished expression of denatured HLA (ρ = 0.289). We studied 52 kidney recipients with preformed anti‐HLA‐Cw donor‐specific antibodies. Those with anti‐native HLA antibodies experienced more acute and chronic antibody‐mediated rejections ( P  = .006 and .03, respectively), and displayed a lower graft survival ( P  = .04). Patients with anti‐native HLA‐Cw antibodies more frequently had previous sensitizing events ( P  < .000001) or plausibility of their antibody profile according to known anti‐native HLA‐Cw eplets ( P  = .0001). Anti‐native but not anti‐denatured HLA‐Cw antibodies are deleterious, which underscores the need for reagents with diminished expression of denatured HLA. Abstract : Antinative but not antidenatured HLA‐Cw antibodies are deleterious in kidney transplantation, which underlines the need for reagents with diminished expression of denatured HLA as antinative HLA‐Cw antibodies lead to random flow cytometry crossmatch results, thus impeding the ability to assess their relevance prior to transplantation.